2023
DOI: 10.1186/s40813-023-00317-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with a carvacrol–cinnamaldehyde–thymol blend on growth performance and intestinal health of nursery pigs

Abstract: Background Stress, herd transfer, and food changes experienced by nursery and fattening pigs can lead to reduced performance, reduced digestion and absorption, and impaired intestinal health. Given the role of essential oils in relieving stress and improving animal welfare, we hypothesized that essential oils may improve pig performance via promoting gut health and gut homeostasis laid by EOs supplementation during nursery continuously impacts performance in fattening pigs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The possible mechanism is that oregano essential oil can create a physical barrier against microorganisms by inducing a higher glycoconjugate production in the gut, ultimately improving disease resistance and growth performance ( 21 , 22 ). Piglets supplemented with 0.1% carvacrol-cinnamaldehyde-thymol blend had enhanced body weight at day 14 and increased ADG and decreased FCR between days 1 and 42 ( 23 ). A previous research has confirmed that plant essential oil can promote the growth and development of animals by increasing nutrient utilization ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism is that oregano essential oil can create a physical barrier against microorganisms by inducing a higher glycoconjugate production in the gut, ultimately improving disease resistance and growth performance ( 21 , 22 ). Piglets supplemented with 0.1% carvacrol-cinnamaldehyde-thymol blend had enhanced body weight at day 14 and increased ADG and decreased FCR between days 1 and 42 ( 23 ). A previous research has confirmed that plant essential oil can promote the growth and development of animals by increasing nutrient utilization ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, marjoram contains numerous bioactive compounds like thymol, carvacrol, and essential oil, which function as antioxidants, antibacterial, and antifungals. The enhancement in growth factors could be ascribed to thymol and carvacrol's presence, which positively affect intestinal flora and possess antibacterial properties, thereby enhancing digestion and absorption in the intestine, potentially playing a crucial role in promoting growth (Ahmadifar et al, 2011 andZhao et al, 2023). Furthermore, these active constituents have the potential to boost digestion efficiency by elevating digestive enzymes, saliva production, enhancing appetite, preventing intestinal infections, alleviating diarrhea and constipation (Baj et al, 2020, Hao et al, 2021, Khorsand et al, 2022, Ili´c et al, 2022, and Kolypetri et al, 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that dietary supplementation with 200 or 300 mg/kg thymol could increase FW, providing a basis for improving pelt yield. Previous studies have shown that supplementing thymol during the nursery period has a beneficial effect on the growth performance of growing pigs ( Zhao et al, 2023 ). Adding 50 mg/kg thymol to the diet can improve the ADG of weaned piglets by promoting intestinal health ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%